2020
DOI: 10.1093/molbev/msaa237
|View full text |Cite
|
Sign up to set email alerts
|

Different Sources of Allelic Variation Drove Repeated Color Pattern Divergence in Cichlid Fishes

Abstract: The adaptive radiations of East African cichlid fish in the Great Lakes Victoria, Malawi, and Tanganyika are well known for their diversity and repeatedly evolved phenotypes. Convergent evolution of melanic horizontal stripes has been linked to a single locus harboring the gene agouti-related peptide 2 (agrp2). However, where and when the causal variants underlying this trait evolved and how they drove phenotypic divergence remained unknown. To test the alternative hypotheses of standing genetic variation vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 97 publications
3
20
0
Order By: Relevance
“…Another potential explanation is that the trait was initially a monogenic trait and that this basis was maintained in Lake Victoria, but that additional stripe alleles only evolved in Lake Malawi. This second hypothesis is supported by previous results suggesting that the stripe-affecting alleles from Lake Victoria are older than the radiation itself and that stripe-associated alleles evolved de novo within Lake Malawi (Urban et al, 2021).…”
Section: The Genetic Basis Of Horizontal Stripes: From Major Effect Loci To Incremental Changessupporting
confidence: 70%
See 1 more Smart Citation
“…Another potential explanation is that the trait was initially a monogenic trait and that this basis was maintained in Lake Victoria, but that additional stripe alleles only evolved in Lake Malawi. This second hypothesis is supported by previous results suggesting that the stripe-affecting alleles from Lake Victoria are older than the radiation itself and that stripe-associated alleles evolved de novo within Lake Malawi (Urban et al, 2021).…”
Section: The Genetic Basis Of Horizontal Stripes: From Major Effect Loci To Incremental Changessupporting
confidence: 70%
“…Based on these results we propose two interpretations explaining the differences of the genetic basis of gain and loss of horizontal stripes we found between the radiations of Lakes Malawi and Victoria. The genetic basis of stripes in Lake Victoria cichlids is well explained by regulatory evolution of two divergent haplotypes of a single intronic interval that evolved prior to the radiation and seems to be responsible for most of the variation in stripe patterns across the ~500 species of this radiation (Kratochwil et al, 2018; Urban et al, 2021). The simple, monogenic basis of horizontal stripes in Lake Victoria cichlids could be therefore the result of a bottleneck during the colonization of Lake Victoria (i.e., other stripe‐affecting alleles did not enter the Lake Victoria radiation with the colonizers).…”
Section: Discussionmentioning
confidence: 99%
“…The protein sequences of WntA and optix are also well conserved within Heliconius suggesting that changes in cis-regulatory elements may drive the evolution of wing patterns (Martin et al, 2012). Cis-regulatory elements are also known to be important drivers of the divergence and subsequent adaptive radiation of color patterns in East African cichlids (Urban et al, 2021). Now that the fundamental genetic basis of conspicuous wing patterns is known in Heliconius, researchers have started looking for similar genetic structure in other butterfly groups to test whether this function arose in this genus or is evolutionarily conserved.…”
Section: Chemical and Genetic Basis Of Insect Warning Colorationmentioning
confidence: 99%
“…Repeated sorting entails repetitive selection on alleles that are identical by descent, regardless of the potential sources of this ancestral variation (Figure 1). A number of recent studies, for example, have highlighted repeated sorting events apparently involving relative ancient polymorphisms (Urban et al, 2021; Van Belleghem et al, 2018) that have been retained in situ across multiple populations. By contrast, several analyses have suggested that such variation can also be secondarily transported, with adaptive alleles introduced to multiple new populations via dispersal (Colosimo et al, 2005; Lescak et al, 2015; Schluter & Conte, 2009; Veale & Russello, 2017).…”
Section: Evolutionary “Sorting”: Repeated Selection On Standing Varia...mentioning
confidence: 99%
“…Examples of convergence: (a) pandas (Hu et al, 2017), (b) seahorses (Li et al, 2021), (c) butterflies (Gallant et al, 2014), (d) Timema stick insects (Villoutreix et al, 2020), (e) Shepherd's‐purse (Yang et al, 2018), (f) Hawaiian crickets (Zhang et al, 2021). Examples of systems illustrating both convergence and sorting: (g) cichlids (Urban et al, 2021), (h) Zelandoperla stoneflies (McCulloch et al, 2021), (i) Gasterosteus sticklebacks (Fang et al, 2020), (j) shortfin molly (Brown et al, 2019). Examples of repeated sorting: (k) Timema stick insects (Lindtke et al, 2017), (l) maize (Guo et al, 2018), (m) salt marsh beetles (Van Belleghem et al, 2018), (n) cichlids (Brawand et al, 2014), (o) Gasterosteus sticklebacks (Magalhaes et al, 2021), (p) sockeye salmon (Veale & Russello, 2017), (q) mountain hares (Giska et al, 2019), (r) steamer ducks (Campagna et al, 2019).…”
Section: Sorting Versus Convergence: a Question Of Scale?mentioning
confidence: 99%